The effects of different vermiwash on the cultivation of Spirulina platensis - Rukshila, K.A.D.T.; Gunawardhana, D.M.M.K.; Varthani, S.; Jeyavanan, K.; Vijayarasa, J.T. (Research gate, 2023)
The Spirulina platensis is quite spread all over the world due to its high nutritional value and Spirulina is capable to grow in various kinds of cultural media. Looking out for natural forms of fertilizers is increasing. This study aimed to determine the influence of various concentrations of vermiwash on the growth of S.platensis. Four concentrations of vermiwash fertilizer used (2, 5, 8 and 11 ml/L) and 10 ml/L of Zarrouk’s medium was used as control. Among the treatments, the highest Spirulina platensis cell concentration was found in the concentration of 5 ml/L and also found to be the most effective concentration to increase in dry matter content of Spirulina. Consequently, it was seen that vermiwash have the potential to replace commercially used medium in S. platensis mass cultures to decrease the costs of production. This formulated vermiwash can be an effective nutrient solution for the mass cultivation of Spirulina platensis.
Keywords: Mass cultivation; Spirulina; Vermiwash fertilizer